Pseudomiopía en paciente de 11 años de edad por exceso de acomodación. - Huacon Guzmán, Karen Jazmin (2022)
The accommodative excess or excess of accommodation is an accommodative dysfunction where the patient has difficulties with tasks related to the relaxation of accommodation and can generate pseudomyopia in patients. The objective is to determine the efficacy of visual therapy in the treatment of excess accommodation, materials and methods. An 11-year-old female patient from the IESS Babahoyo General Hospital, she reported headaches for more than 4 months. Tests were carried out to evaluate the patient's accommodative system, based on the Scientific, quantitative method, with a type of applied level research. Results Due to the accommodation problem presented by the patient, it was decided to follow a treatment based on visual therapy with a duration of 18 weeks with the aim of changing visual hygiene habits, eliminating symptoms, normalizing accommodation values and integrating them with vergences and ocular motility. As a final result, we can ensure that visual therapy has managed to restore the abnormal values of the accommodative system, as well as the patient's visual acuity. After the last week of vision therapy, controls were made every 2 months for 3 additional sessions, resulting in normality in the exams and improvement in visual skills Conclusions: Vision therapy has managed to normalize the values of the accommodative system, eliminating the symptoms.